Why Worry About Corruption?. (Economic Issues; Economic Issues ;, 1997)
This pamphlet focuses exclusively on corrupt public practices. It liststhe potential causes and consequences of public corruption and presentsrecent evidence on the extent to which corruption affects investment,economic growth, and government expenditure choices. The evidence presented here suggests that corruption may have considerable adverseeffects on economic growth by reducing private investment and perhaps byworsening the composition of public expenditure.